2023
DOI: 10.1021/acsnano.3c00866
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Trapping of Single Atoms onto a Metal Carbide Surface

Abstract: Controlling atomic adjustment of single-atom catalysts (SACs) can directly change its local configuration, regulate the energy barrier of intermediates, and further optimize reaction pathways. Herein, we report an atom manipulating process to synthesize Ni atoms stabilized on vanadium carbide (Ni SA -VC) through a nanofiber-medium thermodynamically driven atomic migration strategy. Experimental and theoretical results systematically reveal the tunable migration pathway of Ni atom from Ni nanoparticles to neigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The above results provided further evidence that the ECR product was formed from bubble CO 2 rather than from electrolyte or carrier. 44,45 In addition, the onset of Sn-MOF/CP (−0.60 V vs RHE) was more positive than SnO 2 /CP (−0.76 V vs RHE), and the current density of ECR on Sn-MOF/CP was higher than that on SnO 2 /CP at the same potential, suggesting that the ECR performance of Sn-MOF/CP was better than SnO 2 /CP. Meanwhile, although the current densities of ECR on Sn-MOF/CP and SnO 2 /CP increased as the applied potential shifted negatively, the current density of ECR on Sn-MOF/CP almost increased linearly, which showed that ECR activity of Sn-MOF/CP enhanced with the negative increase of the applied potential.…”
Section: Resultsmentioning
confidence: 97%
“…The above results provided further evidence that the ECR product was formed from bubble CO 2 rather than from electrolyte or carrier. 44,45 In addition, the onset of Sn-MOF/CP (−0.60 V vs RHE) was more positive than SnO 2 /CP (−0.76 V vs RHE), and the current density of ECR on Sn-MOF/CP was higher than that on SnO 2 /CP at the same potential, suggesting that the ECR performance of Sn-MOF/CP was better than SnO 2 /CP. Meanwhile, although the current densities of ECR on Sn-MOF/CP and SnO 2 /CP increased as the applied potential shifted negatively, the current density of ECR on Sn-MOF/CP almost increased linearly, which showed that ECR activity of Sn-MOF/CP enhanced with the negative increase of the applied potential.…”
Section: Resultsmentioning
confidence: 97%
“…21 MOFs are often used as precursors to obtain "final products" by various calcination treatments to optimize conductivity and electrocatalytic performance. [22][23][24] Such post-processing methods, however, often have the disadvantages of high input, high energy consumption and low yield. 25 Therefore, it is urgent to reasonably decorate the structure of original MOFs to overcome the development bottleneck of electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Various metal sulfides are extensively employed in CO 2 ER; the component sulfur element can promote water activation and dissociation to form adsorbed H species (H*) that can react with the CO 2 molecule. , Group VB vanadium compounds, such as vanadium oxide (VO 2 ) and vanadium carbide (VC), have been exploited as an effective component of the catalyst in CO 2 ER. Vanadium ions (V 4+ and V 5+ ) can be utilized as a dopant to tune the local charge distribution of the pristine catalyst for improving the selectivity of a desired product in CO 2 ER. , Therefore, we can expect that VS 2 , one of the group VB transition-metal dichalcogenides (TMDs) possessing high conductivity, has potential application in CO 2 ER.…”
Section: Introductionmentioning
confidence: 99%